2014
DOI: 10.1111/jipb.12106
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the ear and the flag leaf to grain filling in durum wheat inferred from the carbon isotope signature: Genotypic and growing conditions effects

Abstract: The ear, together with the flag leaf, is believed to play a major role as a source of assimilates during grain filling in C 3 cereals. However, the intrusive nature of most of the available methodologies prevents reaching conclusive results in this regard. This study compares the carbon isotope composition (d 13 C) in its natural abundance in the watersoluble fractions of the flag leaf blade and the ear with the d 13 Cof mature kernels to assess the relative contribution of both organs to grain filling in duru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 60 publications
10
84
0
1
Order By: Relevance
“…The inference of the sources of assimilates were based on single season data of 2014 due to missing grain 13 C data for 2013, hence some caution should be given here. However, Sanchez-Bragado et al (2014a) arrived at similar conclusions using one season of data. But, if indeed, the assimilates for grain filling under drought are exported from stored assimilates then there is a high 13 C fractionation during phloem transport.…”
Section: Carbon Isotope Discrimination In Grain and Flag Leavessupporting
confidence: 77%
“…The inference of the sources of assimilates were based on single season data of 2014 due to missing grain 13 C data for 2013, hence some caution should be given here. However, Sanchez-Bragado et al (2014a) arrived at similar conclusions using one season of data. But, if indeed, the assimilates for grain filling under drought are exported from stored assimilates then there is a high 13 C fractionation during phloem transport.…”
Section: Carbon Isotope Discrimination In Grain and Flag Leavessupporting
confidence: 77%
“…Although it has been reported that grain weight remained unchanged in durum wheat cultivars grown in different periods during the 20th century (Royo et al, 2007), semi-dwarf cultivars responded positively to water input during grain filling using it to raise the weight of their grains. This result can be explained by the observed increase in potential grain weight (Álvaro et al, 2008a), and grain filling duration (Royo et al, 2008) of modern durum cultivars in comparison with the old ones, and the improvement of the sink capacity caused by the introduction of dwarfing genes, which augmented the constraint to grain filling due to the source of assimilates (Álvaro et al, 2008c;Maydup et al, 2012;Sanchez-Bragado et al, 2014). In consequence, as semidwarf cultivars are more source-limited than tall ones and have a longer grain filling period, they could take advantage of favourable water input conditions after anthesis for the production of heavier grains.…”
Section: Discussionmentioning
confidence: 73%
“…Carbon isotope tracer is widely used in the study of plant photosynthesis and respiration (Nguyen et al 1999, Ekblad and Högberg 2000, Ostle et al 2000, Kuzyakov and Domanski 2002, Thornton et al 2004, Matsuhashi et al 2006, Comstedt et al 2007, Sanchez-Bragado et al 2014. Photosynthetic C-labelling of wheat flag leaves and intact plants using carbon isotopes ( 14 C, 13 C) is the main technique in studying the distribution of carbon assimilates.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic C-labelling of wheat flag leaves and intact plants using carbon isotopes ( 14 C, 13 C) is the main technique in studying the distribution of carbon assimilates. Sanchez-Bragado (2014) studied the spike contribution to grain amongst different varieties using 13 C-labelling. We have studied 14 C-photosynthate distribution before and after anthesis, and results show that moderate water deficit can raise the spike carbon assimilation activity of wheat and accelerate photosynthate transport to grain in early grain filling, with subsequent maintenance of relatively high grain yields (Ren et al 2012, Zhang et al 2013.…”
Section: Introductionmentioning
confidence: 99%